How do physiotherapists perceive their role in work ability assessments? A prospective focus group study. Issue 3 (16th April 2013) - Stigmar, Kjerstin; Ekdahl, Charlottle; Borgquist, Lars; Grahn, Birgitta
<x content-type="archive" xml:space="preserve">Abstract</x> Background Work ability and work ability assessments have become important both in health care and in relation to granting sick leave. There are different interpretations of work ability among the different professionals involved, and there is no consensus on how work ability should be assessed. Aim The aim was to analyse how a group of experienced and specially trained physiotherapists (PTs) in primary health care (PHC) perceived their professional role in work ability assessments during 14 months. Methods We conducted a prospective focus group study and applied qualitative content analysis to the data. Findings There was a need to emphasise the PTs' role both within PHC and also in relation to others involved. The PHC organisation was not really prepared to direct work-disabled patients to PTs before physicians. In addition, the PTs themselves needed to reorganise to better meet the requirements. The PTs underlined the advantage of their frequent and extended meetings with patients. This made it possible to assess, follow and facilitate work ability and to determine patients' resources. The PTs believed that they could contribute to structured assessments, which was positive for themselves and also in their communication with physicians and patients. The PTs later took more initiatives in work ability questions and believed that they could be responsible for work ability assessments to a greater extent. They found it most valuable to have had the opportunity to reflect on work ability, while working in the focus groups, and also to have been the subjects for further education. This made them more prepared to handle work ability questions when compared with other colleagues.